Preoperative Arterial and Venous Cannulation in Redo Cardiac Surgery: From the Safety and Cost-effectiveness Points of View - Yildiz,Yahya (2020)
Abstract Objective: To investigate the safety and cost-effectiveness of preoperative cannulation and conventional approach techniques. Methods: Sixty-one patients who underwent redo open cardiac procedures between September 2015 and November 2018 were divided into two groups - Group A (n: 30), patients who underwent conventional cannulation after sternotomy, and Group B (n: 31), those who underwent cannulation before sternotomy. Patients were evaluated retrospectively for general complication rates and total hospital costs. Results: Mortality occurred in four patients from Group A and in one patient from Group B. Four patients required extracorporeal membrane oxygenation (ECMO) in Group A, whereas two required ECMO in Group B. Duration of total operation, cardiopulmonary bypass, and cross-clamp times were longer in the conventional surgery group than in the pre-sternotomy cannulation group (420.29±188.84 vs. 314.77±187.38, P=0.036; 171.87±85.59 vs. 141.7±82.47, P=0.089; and 102.94±70.67 vs. 60.97±52.81, P=0.009; respectively). Total blood and blood product usage were higher in Group A than in Group B. Postoperative intensive care unit stay was 62.77±145.3 hours vs. 25.13±73.11 hours, ventilation time was 5.16±5.09 hours vs. 3.03±2.78 hours, duration of ward stay was 5.23±2.52 days vs. 5.57±2.16 days, and duration of hospital stay was 9.58±5.85 days vs. 9.8±5.31 days in conventional sternotomy and pre-sternotomy cannulation groups, respectively. Total hospital costs were calculated 35863.52±20803.99 Turkish Liras (TL) in Group A and 25744.74±16472.03 TL in Group B (P=0,042). Conclusion: Venous and arterial cannulations before sternotomy decreased myocardial injury and complication rates, blood and blood product usage, hospital stay, and, consequently, hospital costs in our modest cohort.